2018
DOI: 10.1111/emre.12324
|View full text |Cite
|
Sign up to set email alerts
|

25 Years of Real Option Empirical Research in Management

Abstract: For several decades, management scholars have extolled the virtues of using real option logic when making decisions under uncertainty. Real option logic suggests that in such situations, firms might be better off deferring or staging investments, reducing potential financial losses, while at the same time securing an option to grow (or abandon) the investment when uncertainty abates. Our analysis of the empirical research published in leading management journals over the past 25 years suggests that while some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 112 publications
(210 reference statements)
0
9
0
Order By: Relevance
“…Within the pertaining literature, the relationship between RO logic and performance is examined from three perspectives [1]. One part of this research suggests that possessing a portfolio of real options or making real option investment decisions improves overall firm value [10][11][12].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Within the pertaining literature, the relationship between RO logic and performance is examined from three perspectives [1]. One part of this research suggests that possessing a portfolio of real options or making real option investment decisions improves overall firm value [10][11][12].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This representation is named the "risk-adjusted" curve. RO empirical research in management published in leading journals over the past 25 years suggests that, while some progress has been made, much more work needs to be done [1]. Several past reviews have indicated that the focus on using RO in practice should be more researched [54,55].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations